Corrosion-resistant 430 stainless steel for water heater plate core and preparation process thereof
By adding rare earth elements Ce and La to 430 stainless steel and using a passivation solution composed of modified Al2O3 and fluorinated epoxy acrylic resin, a dense and flexible passivation film is formed, which solves the problem of insufficient density of the passivation film of 430 stainless steel and improves the corrosion resistance and service life of the water heater core.
Patent Information
- Application Number
- CN202611562942.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-10-10
- Publication Date
- 2026-11-06
AI Technical Summary
In existing technologies, 430 stainless steel does not contain molybdenum, resulting in insufficient density of the passivation film. Chloride ions can easily penetrate the passivation film and form pitting corrosion at surface defects, leading to a reduction in the service life of the water heater core.
Rare earth elements Ce and La are added during the preparation of 430 stainless steel to improve pitting corrosion resistance by forming high-melting-point rare earth compounds that float to the surface. At the same time, a passivation liquid composed of modified Al2O3, fluorinated epoxy acrylate resin and 2-aminothiazole is used to form a dense and flexible passivation film, which enhances the adhesion to the stainless steel substrate.
It improves the corrosion resistance of 430 stainless steel, extends the service life of the water heater core, and enhances the corrosion resistance, flexibility, and weather resistance of the passivation film.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of stainless steel preparation technology, specifically to corrosion-resistant 430 stainless steel for water heater cores and its preparation process. Background Technology
[0002] The core heat exchange plate, also known as the heat exchange plate or heat absorption plate, is the core heat exchange and pressure-bearing component of a flat-plate solar water heater. It has the function of transferring heat to cold water and directly determines the thermal efficiency of the water heater.
[0003] In traditional technology, 304 stainless steel (austenitic stainless steel) is usually used as the core material. However, 304 stainless steel contains nickel, which increases its cost and causes its price to fluctuate greatly due to the influence of nickel. Therefore, existing technologies are gradually replacing 304 stainless steel with 430 stainless steel. However, 430 stainless steel does not contain molybdenum, which results in insufficient density of the passivation film. Chloride ions can easily penetrate the passivation film and form pits at surface defects, which can then rapidly expand inward, leading to a reduction in the service life of the water heater core material.
[0004] Therefore, this invention proposes a corrosion-resistant 430 stainless steel for water heater cores and its preparation process, thereby improving the service life of water heater cores by enhancing the corrosion resistance of 430 stainless steel. Summary of the Invention
[0005] The purpose of this invention is to provide corrosion-resistant 430 stainless steel for water heater cores and its preparation process, so as to solve the problems raised in the prior art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a preparation process for corrosion-resistant 430 stainless steel for water heater core plates, comprising the following steps: Step 1: Mix raw materials other than rare earth elements, melt them, heat them, add rare earth elements under nitrogen atmosphere protection, heat them again, pour and cool them to obtain stainless steel billet; Step 2: The stainless steel billet is subjected to heat treatment, rough rolling, finish rolling, annealing, pickling and drying in sequence to obtain 430 stainless steel matrix; Step 3: Coat the surface of the 430 stainless steel substrate with passivation solution, dry, and let stand to form a passivation film, thus obtaining corrosion-resistant 430 stainless steel.
[0007] Furthermore, the rare earth elements are Ce (cerium) and La (lanthanum).
[0008] Furthermore, the stainless steel billet comprises the following mass percentages: 0.04~0.10% C (carbon), 0.25~0.65% Si (silicon), 0.10~0.15% Mn (manganese), 0.010~0.015% P (phosphorus), 0.09~0.12% Ni (nickel), 16.0~17.0% Cr (chromium), 0.010~0.012% Ce (cerium), 0.005~0.007% La (lanthanum), with the balance being Fe (iron).
[0009] Furthermore, in step 1, the melting temperature is 1530~1560℃; In step 1, the process conditions for heat preservation are: temperature 1530~1560℃, time 4.5~5.5min.
[0010] Furthermore, in step 2, the heat treatment process conditions are: temperature 1100~1160℃, time 200~220min; The roughing rolling process conditions are: temperature 1040~1060℃, reduction rate 40~50%; The finishing rolling process conditions are: temperature 830~860℃, reduction rate 50~60%; The annealing process conditions are: temperature 850~860℃, holding time 1.0~1.2min / mm; The heat preservation time is based on the thickness of the stainless steel billet.
[0011] Furthermore, in step 2, a sulfuric acid solution with a mass concentration of 100~200g / L is used for pickling, and the pickling temperature is 60~70℃; In step 2, the drying process conditions are: temperature 70~90℃, time 2~3h.
[0012] Furthermore, in step 3, the drying process conditions are: temperature 115~125℃, time 1~2min; In step 3, let it stand at 20~30℃ for 20~24 hours.
[0013] Furthermore, in step 3, the thickness of the passivation film is 0.4~0.8μm.
[0014] In the above technical solution, rare earth elements Ce and La are added. During the preparation of stainless steel, rare earth elements act as strong deoxidizers and desulfurizers, which can react with oxygen and sulfur to generate high-melting-point rare earth compounds that float to the surface, thereby improving the pitting corrosion resistance of stainless steel. In addition, the addition of Ce can increase the equiaxed grain ratio of stainless steel, effectively refine the grains, prevent crack propagation, and thus improve the strength and toughness of stainless steel.
[0015] Furthermore, the passivation solution comprises the following components by mass: 15~30 g / L modified Al2O3, 220~260 g / L fluorinated epoxy acrylate resin, 8~15 g / L 2-aminothiazole, and 1.0~1.3 g / L nickel acetate, with deionized water as the solvent.
[0016] Furthermore, the modified Al2O3 is prepared by the following process: S1: Under a nitrogen atmosphere, 1,2-diaminoimidazole and tetrahydrofuran were mixed, and 3-isocyanate-propyltriethoxysilane was added while stirring. The mixture was heated and stirred to react. After the reaction was completed, the mixture was rotary evaporated to obtain an imidazole coupling agent. S2: Mix carboxymethyl chitosan, imidazole coupling agent, and ethanol aqueous solution, adjust the pH to 4.0~4.5 with glacial acetic acid, disperse by ultrasonication, hydrolyze by stirring, react by stirring in a water bath, centrifuge and dry after the reaction is completed to obtain modified carboxymethyl chitosan; S3: Mix deionized water and modified carboxymethyl chitosan, stir evenly, add Al2O3, heat and stir to react, and obtain modified Al2O3.
[0017] Furthermore, in S1, the ratio of 1,2-diaminoimidazole, tetrahydrofuran, and 3-isocyanate-propyltriethoxysilane is (3~5) g: (45~55) mL: (6~10) g.
[0018] Furthermore, in S1, the process conditions for heating and stirring reaction are: temperature 45~55℃, stirring speed 40~60r / min, and reaction time 1.8~2.2h.
[0019] Furthermore, in S1, the rotary evaporation process conditions are: temperature 30~45℃, time 15~25min.
[0020] Furthermore, in S2, the ratio of carboxymethyl chitosan, imidazole coupling agent, and ethanol aqueous solution is (1~3) g: (3~9) g: 100 mL; The ethanol aqueous solution contains 90-97% ethanol by mass.
[0021] Furthermore, in S2, the ultrasonic dispersion process conditions are: temperature 25~30℃, time 15~20min, frequency 25~35kHz; In S2, the stirring hydrolysis temperature is 25~30℃, the time is 20~30min, and the rotation speed is 30~50r / min; In S2, the process conditions for the water bath stirring reaction are: temperature 35~45℃, stirring speed 50~60r / min, and reaction time 4~6h.
[0022] Furthermore, in S2, the centrifugation process conditions are: rotation speed 3000~5000 r / min, time 6~10 min; In S2, the drying process conditions are: temperature 50~60℃, time 40~50min.
[0023] Furthermore, in S3, the ratio of deionized water, modified carboxymethyl chitosan, and Al2O3 is 35mL:(0.5~1.0)g:(0.5~1.0)g.
[0024] Furthermore, in S3, the process conditions for heating and stirring reaction are: temperature 35~45℃, stirring speed 50~60r / min, and reaction time 1.5~2.5h.
[0025] In the above technical solution, firstly, the primary amino group of 1,2-diaminoimidazolium undergoes nucleophilic addition with the isocyanate of 3-isocyanate-propyltriethoxysilane to generate an imidazolium coupling agent containing a urea bond; then, the triethoxysilyl group in the imidazolium coupling agent is hydrolyzed to generate silanol groups, which undergo dehydration condensation with the hydroxyl groups of carboxymethyl chitosan to form Si-OC bonds, thus obtaining modified carboxymethyl chitosan; finally, the unreacted silanol groups undergo dehydration condensation with the hydroxyl groups on the surface of Al2O3, and at the same time, the carboxyl groups in carboxymethyl chitosan can form hydrogen bonds with the hydroxyl groups on the surface of Al2O3 to obtain modified Al2O3.
[0026] Furthermore, the preparation process of the fluorinated epoxy acrylate resin is as follows: Under a nitrogen atmosphere, xylene and butyl acetate are mixed and heated to 80-90°C. Then, dodecafluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate and azobisisobutyronitrile are added over 3-4 hours. The mixture is kept at this temperature to obtain a fluorinated epoxy acrylic resin.
[0027] Furthermore, the mass ratio of xylene, butyl acetate, dodecafluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate, and azobisisobutyronitrile is (2.0~3.0):1:(0.8~1.2):(0.6~0.8):(0.8~1.0):(0.08~0.12).
[0028] Furthermore, the process conditions for the heat preservation reaction are: temperature 82~85℃, time 3~4h.
[0029] In the above technical solution, under the action of azobisisobutyronitrile, dodecafluoroheptyl methacrylate, butyl acrylate, and glycidyl methacrylate undergo free radical copolymerization, introducing long-term fluoroalkyl side chains and epoxy groups. The long-term fluoroalkyl side chains have extremely low surface energy, which can make the passivation film have amphiphilicity, effectively blocking the penetration of chloride ions in water. The epoxy groups facilitate the reaction with the primary amino group of 2-aminothiazole during the curing process to form crosslinks, introducing thiazole rings. The nitrogen and sulfur atoms on the thiazole rings have lone pairs of electrons, which can form coordination bonds with the Fe atoms on the surface of 430 ferritic stainless steel, enhancing the bonding force between the passivation film and the 430 ferritic stainless steel substrate, which is beneficial to improving the corrosion resistance, flexibility, and weather resistance of the passivation film.
[0030] Compared with the prior art, the beneficial effects of the present invention are: 1. In this invention, a silane coupling agent containing an imidazole ring, namely an imidazole coupling agent, is prepared by nucleophilic addition reaction. This imidazole coupling agent is then combined with carboxymethyl chitosan and Al2O3 to obtain modified Al2O3. The imidazole ring can be adsorbed onto the metal surface through coordination, enhancing the bonding force between the passivation film and the stainless steel substrate. Carboxymethyl chitosan is a high-performance organic film-forming agent, which is beneficial for forming a continuous and flexible passivation film. Al2O3, as a functional filler, can improve the hardness and wear resistance of the passivation film and also block the penetration of corrosive media. The synergistic effect of the three is beneficial for further enhancing the corrosion resistance of the passivation film. In addition, Ni generated by the dissociation of nickel acetate in the passivation solution 2+ On the one hand, it can participate in the formation process of the passivation film, Ni 2+ It can react with hydroxides on the surface of 430 stainless steel substrates to make the passivation film denser and more uniform. On the other hand, it can act as a Lewis acid catalyst to promote the ring-opening reaction of 2-aminothiazole and epoxy acrylate resin, increasing the crosslinking density of the coating and thus improving the performance of stainless steel in Cl-containing environments. - Resistance to pitting corrosion in the environment.
[0031] 2. In this invention, a fluorinated epoxy acrylate resin was prepared by free radical copolymerization. This resin was then mixed with modified Al2O3, 2-aminothiazole, and nickel acetate to form a passivation film, which was then coated onto the surface of a 430 ferritic stainless steel substrate. During the curing process, the primary amino group of the 2-aminothiazole reacts with the epoxy group of the fluorinated epoxy acrylate resin to form a crosslink, which facilitates the introduction of thiazole rings. The nitrogen and sulfur atoms on the thiazole rings have lone pairs of electrons, which can form coordinate bonds with the Fe atoms on the surface of the 430 ferritic stainless steel, thereby enhancing the bonding force between the passivation film and the 430 ferritic stainless steel substrate. This is beneficial for improving the corrosion resistance, flexibility, and weather resistance of the passivation film.
[0032] 3. In this invention, rare earth elements Ce and La are added to the stainless steel billet. During the preparation of stainless steel, rare earth elements act as strong deoxidizers and desulfurizers, which can react with oxygen and sulfur to generate high-melting-point rare earth compounds that float to the surface, thereby improving the pitting corrosion resistance of stainless steel. In addition, the addition of Ce can increase the equiaxed grain ratio of stainless steel, effectively refine the grains, prevent crack propagation, and thus improve the strength and toughness of stainless steel. Detailed Implementation
[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0034] In the following specific implementation, Cerium powder, 300 mesh, 99.9% purity; Lanthanum powder, 300 mesh, 99.5% purity; Al2O3, α phase, average particle size 30nm; Acrylic resin, model SG-1601.
[0035] Example 1: The manufacturing process of corrosion-resistant 430 stainless steel for water heater core includes the following steps: (1) Preparation of modified Al2O3: S1: Under a nitrogen atmosphere, 1,2-diaminoimidazole and tetrahydrofuran were mixed, and 3-isocyanate-propyltriethoxysilane was added while stirring. The mixture was heated to 55°C and stirred at 60 r / min for 2.2 h. After the reaction was completed, the mixture was rotary evaporated at 45°C for 25 min to obtain the imidazole coupling agent. S2: Carboxymethyl chitosan, the imidazole coupling agent, and a 97% ethanol aqueous solution were mixed at a ratio of 3 g:9 g:100 mL. The pH was adjusted to 4.5 with glacial acetic acid. The mixture was ultrasonically dispersed at 30°C and 35 kHz for 20 min, then hydrolyzed by stirring at 30°C and 50 r / min for 30 min. Finally, the mixture was stirred in a water bath at 45°C and 60 r / min for 6 h. After completion, centrifugation and drying were performed to obtain modified carboxymethyl chitosan; S3: Deionized water and modified carboxymethyl chitosan were mixed and stirred evenly, Al2O3 was added, and the mixture was heated to 45℃ and stirred at 60 r / min for 2.5 h to obtain modified Al2O3; In S1, the ratio of 1,2-diaminoimidazole, tetrahydrofuran, and 3-isocyanate-propyltriethoxysilane was 5 g: 55 mL: 10 g; In S2, the centrifugation conditions were: 5000 r / min for 10 min; In S2, the drying conditions were: 60℃ for 50 min; In S3, the ratio of deionized water, modified carboxymethyl chitosan, and Al2O3 was 35 mL: 1.0 g: 1.0 g; (2) Preparation of fluorinated epoxy acrylic resin: Under a nitrogen atmosphere, xylene and butyl acetate were mixed and heated to 90°C. Then, dodecafluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate, and azobisisobutyronitrile were added over 4 hours. The mixture was then kept at 85°C for 4 hours to obtain a fluorinated epoxy acrylic resin. The mass ratio of xylene, butyl acetate, dodecafluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate, and azobisisobutyronitrile was 3.0:1:1.2:0.8:1.0:0.12. (3) Preparation of corrosion-resistant 430 stainless steel: Step 1: Mix raw materials except rare earth elements, melt at 1560℃, then hold at that temperature for 5.5 min. Add cerium powder and lanthanum powder under a nitrogen atmosphere, and hold at 1560℃ again for 5.5 min. Cast and cool to obtain a stainless steel billet. Step 2: Perform heat treatment, rough rolling, finish rolling, annealing, pickling, and drying on the stainless steel billet to obtain a 430 stainless steel substrate. Step 3: Coat the surface of the 430 stainless steel substrate with a passivation solution, dry, and allow to stand to form a 0.8 μm thick passivation film, obtaining corrosion-resistant 430 stainless steel. The stainless steel billet contains the following composition by mass percentage: 0.10% C, 0.65% Si, 0.15% Mn, 0.015% P, 0.12% Ni, 17.0% Cr, 0.012% Ce, 0.007% La, with the remainder being Fe. In Step 2, the heat treatment process conditions are as follows: The process conditions for rough rolling are: temperature 1160℃, time 220min; the process conditions for finishing rolling are: temperature 1060℃, reduction rate 50%; the process conditions for finishing rolling are: temperature 860℃, reduction rate 60%; the process conditions for annealing are: temperature 860℃, holding time 1.2min / mm; the holding time is based on the thickness of the stainless steel billet; in step 2, pickling is performed using a sulfuric acid solution with a mass concentration of 200g / L at a pickling temperature of 70℃; in step 2, the drying process conditions are: temperature 90℃, time 3h; in step 3, the drying process conditions are: temperature 125℃, time 2min; in step 3, the billet is left to stand at 30℃ for 24h; in step 3, the passivation solution includes the following mass components: 30g / L modified Al2O3, 260g / L fluorinated epoxy acrylate resin, 15g / L 2-aminothiazole, 1.3g / L nickel acetate, and the solvent is deionized water.
[0036] Example 2: The preparation process of corrosion-resistant 430 stainless steel for water heater core includes the following steps: (1) Preparation of modified Al2O3: S1: Under a nitrogen atmosphere, 1,2-diaminoimidazolium and tetrahydrofuran were mixed, and 3-isocyanate-propyltriethoxysilane was added while stirring. The mixture was heated to 50°C and stirred at 50 r / min for 2.0 h. After the reaction, the mixture was rotary evaporated at 35°C for 20 min to obtain the imidazole coupling agent. S2: Carboxymethyl chitosan, the imidazole coupling agent, and a 94% ethanol aqueous solution were mixed at a ratio of 2 g:6 g:100 mL. The pH was adjusted to 4.3 with glacial acetic acid. The mixture was ultrasonically dispersed at 28°C and 30 kHz for 18 min, hydrolyzed by stirring at 28°C and 40 r / min for 25 min, and then reacted in a water bath at 40°C and 55 r / min for 5 h. After centrifugation and drying, modified carboxymethyl chitosan is obtained; S3: Deionized water and modified carboxymethyl chitosan are mixed and stirred evenly, Al2O3 is added, heated to 40℃, and stirred at 55r / min for 2.0h to obtain modified Al2O3; In S1, the ratio of 1,2-diaminoimidazolium, tetrahydrofuran, and 3-isocyanate-propyltriethoxysilane is 4g:50mL:8g; In S2, the centrifugation process conditions are: speed 4000r / min, time 8min; In S2, the drying process conditions are: temperature 55℃, time 45min; In S3, the ratio of deionized water, modified carboxymethyl chitosan, and Al2O3 is 35mL:0.8g:0.8g; (2) Preparation of fluorinated epoxy acrylic resin: Under a nitrogen atmosphere, xylene and butyl acetate were mixed and heated to 85°C. Then, dodecyl fluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate, and azobisisobutyronitrile were added over 3.5 hours. The mixture was then kept at 83°C for 3.5 hours to obtain a fluorinated epoxy acrylic resin. The mass ratio of xylene, butyl acetate, dodecyl fluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate, and azobisisobutyronitrile was 2.5:1:1.0:0.7:0.9:0.10. (3) Preparation of corrosion-resistant 430 stainless steel: Step 1: Mix raw materials except rare earth elements, melt at 1545℃, then hold at that temperature for 5.0 min. Add cerium powder and lanthanum powder under nitrogen atmosphere protection, and hold at 1545℃ again for 5.0 min. Cast and cool to obtain a stainless steel billet. Step 2: Perform heat treatment, rough rolling, finish rolling, annealing, pickling, and drying on the stainless steel billet to obtain a 430 stainless steel substrate. Step 3: Coat the surface of the 430 stainless steel substrate with passivation solution, dry, and let stand to form a 0.6 μm thick passivation film to obtain corrosion-resistant 430 stainless steel. The stainless steel billet contains the following mass composition: by mass percentage, 0.08% C, 0.45% Si, 0.13% Mn, 0.013% P, 0.11% Ni, 16.5% Cr, 0.011% Ce, 0.006% La, with the remainder being Fe. In Step 2, the heat treatment process conditions are: temperature... The process conditions for rough rolling are: temperature 1050℃, reduction rate 45%; the process conditions for finish rolling are: temperature 845℃, reduction rate 55%; the process conditions for annealing are: temperature 855℃, holding time 1.1min / mm; the holding time is based on the thickness of the stainless steel billet; in step 2, pickling is performed using a sulfuric acid solution with a mass concentration of 150g / L at a pickling temperature of 65℃; in step 2, the drying process conditions are: temperature 80℃, time 2.5h; in step 3, the drying process conditions are: temperature 120℃, time 1.5min; in step 3, the billet is left to stand at 25℃ for 22h; in step 3, the passivation solution includes the following mass components: 20g / L modified Al2O3, 240g / L fluorinated epoxy acrylate resin, 12g / L 2-aminothiazole, 1.2g / L nickel acetate, and deionized water as the solvent.
[0037] Example 3: The preparation process of corrosion-resistant 430 stainless steel for water heater core includes the following steps: (1) Preparation of modified Al2O3: S1: Under a nitrogen atmosphere, 1,2-diaminoimidazolium and tetrahydrofuran were mixed, and 3-isocyanate-propyltriethoxysilane was added while stirring. The mixture was heated to 45°C and stirred at 40 r / min for 1.8 h. After the reaction, the mixture was rotary evaporated at 30°C for 15 min to obtain the imidazole coupling agent. S2: Carboxymethyl chitosan, the imidazole coupling agent, and a 90% ethanol aqueous solution were mixed at a ratio of 1 g:3 g:100 mL. The pH was adjusted to 4.0 with glacial acetic acid. The mixture was ultrasonically dispersed at 25°C and 25 kHz for 15 min, hydrolyzed by stirring at 25°C and 30 r / min for 20 min, and then reacted in a water bath at 35°C and 50 r / min for 4 h. After centrifugation and drying, modified carboxymethyl chitosan is obtained; S3: Deionized water and modified carboxymethyl chitosan are mixed and stirred evenly, Al2O3 is added, heated to 35℃, and stirred at 50r / min for 1.5h to obtain modified Al2O3; In S1, the ratio of 1,2-diaminoimidazole, tetrahydrofuran, and 3-isocyanate-propyltriethoxysilane is 3g:45mL:6g; In S2, the centrifugation process conditions are: speed 3000r / min, time 6min; In S2, the drying process conditions are: temperature 50℃, time 40min; In S3, the ratio of deionized water, modified carboxymethyl chitosan, and Al2O3 is 35mL:0.5g:0.5g; (2) Preparation of fluorinated epoxy acrylic resin: Under a nitrogen atmosphere, xylene and butyl acetate were mixed and heated to 80°C. Then, dodecyl fluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate, and azobisisobutyronitrile were added over 3 hours. The mixture was then kept at 82°C for 3 hours to obtain a fluorinated epoxy acrylic resin. The mass ratio of xylene, butyl acetate, dodecyl fluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate, and azobisisobutyronitrile was 2.0:1:0.8:0.6:0.8:0.08. (3) Preparation of corrosion-resistant 430 stainless steel: Step 1: Mix raw materials except rare earth elements, melt at 1530℃, then hold at that temperature for 4.5 min. Add cerium powder and lanthanum powder under a nitrogen atmosphere, and hold at 1530℃ again for 4.5 min. Cast and cool to obtain a stainless steel billet. Step 2: Perform heat treatment, rough rolling, finish rolling, annealing, pickling, and drying on the stainless steel billet to obtain a 430 stainless steel substrate. Step 3: Coat the surface of the 430 stainless steel substrate with a passivation solution, dry, and allow to stand to form a 0.4 μm thick passivation film, obtaining corrosion-resistant 430 stainless steel. The stainless steel billet contains the following composition by mass percentage: 0.04% C, 0.25% Si, 0.10% Mn, 0.010% P, 0.09% Ni, 16.0% Cr, 0.010% Ce, 0.005% La, with the remainder being Fe. In Step 2, the heat treatment process conditions are as follows: The process conditions for rough rolling are: temperature 1100℃, time 200min; the process conditions for finishing rolling are: temperature 1040℃, reduction rate 40%; the process conditions for finishing rolling are: temperature 830℃, reduction rate 50%; the process conditions for annealing are: temperature 850℃, holding time 1.0min / mm; the holding time is based on the thickness of the stainless steel billet; in step 2, pickling is performed using a sulfuric acid solution with a mass concentration of 100g / L at a pickling temperature of 60℃; in step 2, the drying process conditions are: temperature 70℃, time 2h; in step 3, the drying process conditions are: temperature 115℃, time 1min; in step 3, the billet is left to stand at 20℃ for 20h; in step 3, the passivation solution includes the following mass components: 15g / L modified Al2O3, 220g / L fluorinated epoxy acrylate resin, 8g / L 2-aminothiazole, 1.0g / L nickel acetate, and the solvent is deionized water.
[0038] Comparative Example 1: Compared with Example 1, no cerium powder and lanthanum powder were added to the stainless steel billet, and all other conditions remained the same as in Example 1, as follows: (1) Preparation of modified Al2O3: S1: Under a nitrogen atmosphere, 1,2-diaminoimidazole and tetrahydrofuran were mixed, and 3-isocyanate-propyltriethoxysilane was added while stirring. The mixture was heated to 55°C and stirred at 60 r / min for 2.2 h. After the reaction was completed, the mixture was rotary evaporated at 45°C for 25 min to obtain the imidazole coupling agent. S2: Carboxymethyl chitosan, the imidazole coupling agent, and a 97% ethanol aqueous solution were mixed at a ratio of 3 g:9 g:100 mL. The pH was adjusted to 4.5 with glacial acetic acid. The mixture was ultrasonically dispersed at 30°C and 35 kHz for 20 min, then hydrolyzed by stirring at 30°C and 50 r / min for 30 min. Finally, the mixture was stirred in a water bath at 45°C and 60 r / min for 6 h. After completion, centrifugation and drying were performed to obtain modified carboxymethyl chitosan; S3: Deionized water and modified carboxymethyl chitosan were mixed and stirred evenly, Al2O3 was added, and the mixture was heated to 45℃ and stirred at 60 r / min for 2.5 h to obtain modified Al2O3; In S1, the ratio of 1,2-diaminoimidazole, tetrahydrofuran, and 3-isocyanate-propyltriethoxysilane was 5 g: 55 mL: 10 g; In S2, the centrifugation conditions were: 5000 r / min for 10 min; In S2, the drying conditions were: 60℃ for 50 min; In S3, the ratio of deionized water, modified carboxymethyl chitosan, and Al2O3 was 35 mL: 1.0 g: 1.0 g; (2) Preparation of fluorinated epoxy acrylic resin: Under a nitrogen atmosphere, xylene and butyl acetate were mixed and heated to 90°C. Then, dodecafluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate, and azobisisobutyronitrile were added over 4 hours. The mixture was then kept at 85°C for 4 hours to obtain a fluorinated epoxy acrylic resin. The mass ratio of xylene, butyl acetate, dodecafluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate, and azobisisobutyronitrile was 3.0:1:1.2:0.8:1.0:0.12. (3) Preparation of corrosion-resistant 430 stainless steel: Step 1: Mix the raw materials, melt them at 1560℃, hold for 5.5 min, pour and cool to obtain a stainless steel billet; Step 2: Perform heat treatment, rough rolling, finish rolling, annealing, pickling and drying on the stainless steel billet in sequence to obtain a 430 stainless steel substrate; Step 3: Coat the surface of the 430 stainless steel substrate with passivation solution, dry, and let stand to form a 0.8 μm thick passivation film to obtain corrosion-resistant 430 stainless steel; The stainless steel billet contains the following mass composition: by mass percentage, 0.10% C, 0.65% Si, 0.15% Mn, 0.015% P, 0.12% Ni, 17.0% Cr, with the remainder being Fe; In Step 2, the heat treatment process conditions are: temperature 1160℃, time 220 min; The rough rolling process conditions are: temperature 10... The rolling process conditions are: 60℃, reduction rate 50%; the finishing rolling process conditions are: temperature 860℃, reduction rate 60%; the annealing process conditions are: temperature 860℃, holding time 1.2min / mm; the holding time is based on the thickness of the stainless steel billet; in step 2, pickling is performed using a sulfuric acid solution with a mass concentration of 200g / L at a pickling temperature of 70℃; in step 2, the drying process conditions are: temperature 90℃, time 3h; in step 3, the drying process conditions are: temperature 125℃, time 2min; in step 3, the billet is left to stand at 30℃ for 24h; in step 3, the passivation solution includes the following mass components: 30g / L modified Al2O3, 260g / L fluorinated epoxy acrylate resin, 15g / L 2-aminothiazole, 1.3g / L nickel acetate, and the solvent is deionized water.
[0039] Comparative Example 2: Compared with Example 1, the modified Al2O3 in the passivation solution was replaced with Al2O3, and the other conditions remained the same as in Example 1, as follows: (1) Preparation of fluorinated epoxy acrylic resin: Under a nitrogen atmosphere, xylene and butyl acetate were mixed and heated to 90°C. Then, dodecafluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate, and azobisisobutyronitrile were added over 4 hours. The mixture was then kept at 85°C for 4 hours to obtain a fluorinated epoxy acrylic resin. The mass ratio of xylene, butyl acetate, dodecafluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate, and azobisisobutyronitrile was 3.0:1:1.2:0.8:1.0:0.12. (2) Preparation of corrosion-resistant 430 stainless steel: Step 1: Mix raw materials except rare earth elements, melt at 1560℃, then hold at that temperature for 5.5 min. Add cerium powder and lanthanum powder under a nitrogen atmosphere, and hold at 1560℃ again for 5.5 min. Cast and cool to obtain a stainless steel billet. Step 2: Perform heat treatment, rough rolling, finish rolling, annealing, pickling, and drying on the stainless steel billet sequentially to obtain a 430 stainless steel substrate. Step 3: Coat the surface of the 430 stainless steel substrate with a passivation solution, dry, and allow to stand to form a 0.8 μm thick passivation film, obtaining corrosion-resistant 430 stainless steel. The stainless steel billet contains the following composition by mass percentage: 0.10% C, 0.65% Si, 0.15% Mn, 0.015% P, 0.12% Ni, 17.0% Cr, 0.012% Ce, 0.007% La, with the remainder being Fe. The heat treatment process conditions in Step 2 are as follows: The process conditions for rough rolling are: temperature 1160℃, time 220min; the process conditions for finishing rolling are: temperature 1060℃, reduction rate 50%; the process conditions for finishing rolling are: temperature 860℃, reduction rate 60%; the process conditions for annealing are: temperature 860℃, holding time 1.2min / mm; the holding time is based on the thickness of the stainless steel billet; in step 2, pickling is performed using a sulfuric acid solution with a mass concentration of 200g / L at a pickling temperature of 70℃; in step 2, the drying process conditions are: temperature 90℃, time 3h; in step 3, the drying process conditions are: temperature 125℃, time 2min; in step 3, the billet is left to stand at 30℃ for 24h; in step 3, the passivation solution includes the following mass components: 30g / L Al2O3, 260g / L fluorinated epoxy acrylate resin, 15g / L 2-aminothiazole, 1.3g / L nickel acetate, and the solvent is deionized water.
[0040] Comparative Example 3: Compared with Example 1, the fluorinated epoxy acrylate resin in the passivation solution was replaced with acrylic resin, and the other conditions remained the same as in Example 1, as follows: (1) Preparation of modified Al2O3: S1: Under a nitrogen atmosphere, 1,2-diaminoimidazole and tetrahydrofuran were mixed, and 3-isocyanate-propyltriethoxysilane was added while stirring. The mixture was heated to 55°C and stirred at 60 r / min for 2.2 h. After the reaction was completed, the mixture was rotary evaporated at 45°C for 25 min to obtain the imidazole coupling agent. S2: Carboxymethyl chitosan, the imidazole coupling agent, and a 97% ethanol aqueous solution were mixed at a ratio of 3 g:9 g:100 mL. The pH was adjusted to 4.5 with glacial acetic acid. The mixture was ultrasonically dispersed at 30°C and 35 kHz for 20 min, then hydrolyzed by stirring at 30°C and 50 r / min for 30 min. Finally, the mixture was stirred in a water bath at 45°C and 60 r / min for 6 h. After completion, centrifugation and drying were performed to obtain modified carboxymethyl chitosan; S3: Deionized water and modified carboxymethyl chitosan were mixed and stirred evenly, Al2O3 was added, and the mixture was heated to 45℃ and stirred at 60 r / min for 2.5 h to obtain modified Al2O3; In S1, the ratio of 1,2-diaminoimidazole, tetrahydrofuran, and 3-isocyanate-propyltriethoxysilane was 5 g: 55 mL: 10 g; In S2, the centrifugation conditions were: 5000 r / min for 10 min; In S2, the drying conditions were: 60℃ for 50 min; In S3, the ratio of deionized water, modified carboxymethyl chitosan, and Al2O3 was 35 mL: 1.0 g: 1.0 g; (2) Preparation of corrosion-resistant 430 stainless steel: Step 1: Mix raw materials except rare earth elements, melt at 1560℃, then hold at that temperature for 5.5 min. Add cerium powder and lanthanum powder under a nitrogen atmosphere, and hold at 1560℃ again for 5.5 min. Cast and cool to obtain a stainless steel billet. Step 2: Perform heat treatment, rough rolling, finish rolling, annealing, pickling, and drying on the stainless steel billet sequentially to obtain a 430 stainless steel substrate. Step 3: Coat the surface of the 430 stainless steel substrate with a passivation solution, dry, and allow to stand to form a 0.8 μm thick passivation film, obtaining corrosion-resistant 430 stainless steel. The stainless steel billet contains the following mass composition: by mass percentage, 0.10% C, 0.65% Si, 0.15% Mn, 0.015% P, 0.12% Ni, 17.0% Cr, 0.012% Ce, 0.007% La, with the remainder being Fe. In Step 2, the heat treatment process conditions... The process conditions for rough rolling are: temperature 1160℃, time 220min; the process conditions for finishing rolling are: temperature 1060℃, reduction rate 50%; the process conditions for finishing rolling are: temperature 860℃, reduction rate 60%; the process conditions for annealing are: temperature 860℃, holding time 1.2min / mm; the holding time is based on the thickness of the stainless steel billet; in step 2, pickling is performed using a sulfuric acid solution with a mass concentration of 200g / L at a pickling temperature of 70℃; in step 2, the drying process conditions are: temperature 90℃, time 3h; in step 3, the drying process conditions are: temperature 125℃, time 2min; in step 3, the billet is left to stand at 30℃ for 24h; in step 3, the passivation solution includes the following mass components: 30g / L modified Al2O3, 260g / L acrylic resin, 15g / L 2-aminothiazole, 1.3g / L nickel acetate, and the solvent is deionized water.
[0041] Comparative Example 4: Compared with Example 1, the modified Al2O3 in the passivation solution was replaced with Al2O3, and the fluorinated epoxy acrylate resin in the passivation solution was replaced with acrylic resin. All other conditions remained the same as in Example 1, as follows: Step 1: Mix raw materials except rare earth elements, melt at 1560℃, then hold at that temperature for 5.5 min. Add cerium powder and lanthanum powder under a nitrogen atmosphere, and hold at 1560℃ again for 5.5 min. Cast and cool to obtain a stainless steel billet. Step 2: Perform heat treatment, rough rolling, finish rolling, annealing, pickling, and drying on the stainless steel billet sequentially to obtain a 430 stainless steel substrate. Step 3: Coat the surface of the 430 stainless steel substrate with a passivation solution, dry, and allow to stand to form a 0.8 μm thick passivation film, obtaining corrosion-resistant 430 stainless steel. The stainless steel billet contains the following composition by mass percentage: 0.10% C, 0.65% Si, 0.15% Mn, 0.015% P, 0.12% Ni, 17.0% Cr, 0.012% Ce, 0.007% La, with the remainder being Fe. The heat treatment process in Step 2... The conditions are as follows: temperature 1160℃, time 220min; rough rolling process conditions are: temperature 1060℃, reduction rate 50%; finish rolling process conditions are: temperature 860℃, reduction rate 60%; annealing process conditions are: temperature 860℃, holding time 1.2min / mm; the holding time is based on the thickness of the stainless steel billet; in step 2, pickling is performed using a sulfuric acid solution with a mass concentration of 200g / L at a pickling temperature of 70℃; in step 2, the drying process conditions are: temperature 90℃, time 3h; in step 3, the drying process conditions are: temperature 125℃, time 2min; in step 3, the billet is left to stand at 30℃ for 24h; in step 3, the passivation solution includes the following mass components: 30g / L Al2O3, 260g / L acrylic resin, 15g / L 2-aminothiazole, 1.3g / L nickel acetate, and the solvent is deionized water.
[0042] Comparative Example 5: Compared with Example 1, no cerium powder and lanthanum powder were added to the stainless steel billet, and no passivation solution was applied. All other conditions remained the same as in Example 1, as follows: Step 1: Mix the raw materials, melt them at 1560℃, hold for 5.5 minutes, pour and cool to obtain a stainless steel billet; Step 2: Perform heat treatment, rough rolling, finish rolling, annealing, pickling and drying on the stainless steel billet in sequence to obtain 430 stainless steel; 430 stainless steel includes the following mass composition: by mass percentage, 0.10% C, 0.65% Si, 0.15% Mn, 0.015% P, 0.12% Ni, 17.0% Cr, with the balance being Fe; In Step 2, the heat treatment process conditions are: temperature 1160℃, time... 220 min; the roughing process conditions are: temperature 1060℃, reduction rate 50%; the finishing process conditions are: temperature 860℃, reduction rate 60%; the annealing process conditions are: temperature 860℃, holding time 1.2 min / mm; the holding time is based on the thickness of the stainless steel billet; in step 2, pickling is performed using a sulfuric acid solution with a mass concentration of 200 g / L at a pickling temperature of 70℃; in step 2, the drying process conditions are: temperature 90℃, time 3 h; in step 3, the drying process conditions are: temperature 125℃, time 2 min.
[0043] experiment: Tensile strength test: The tensile strength of the corrosion-resistant 430 stainless steel was tested according to GB / T228.1-2021, with a tensile speed of 1 mm / min; Corrosion resistance test: Referring to ASTM-B117-2011, a 6% NaCl solution was used and tested at 37°C for 720 hours to determine its corrosion rate and characterize its corrosion resistance. Adhesion test: Referring to GB / T9286-2021, the adhesion level of the passivation film on the surface of 430 stainless steel substrate was tested to characterize its adhesion performance. A blank control group was also set up in the experiment. The blank control group was a 430 stainless steel substrate without passivation solution prepared according to the process parameters of Example 1. The table below shows the performance test results of corrosion-resistant 430 stainless steel;
[0044] Based on the data in the table above, the following conclusions can be drawn: Compared with Example 1, no cerium powder and lanthanum powder were added to the stainless steel billet of Comparative Example 1, and the tensile strength of the corrosion-resistant 430 stainless steel produced was significantly reduced. Compared with Example 1, Comparative Example 2 replaced the modified Al2O3 in the passivation solution with Al2O3, and Comparative Example 3 replaced the fluorinated epoxy acrylate resin in the passivation solution with acrylic resin. The tensile strength of the corrosion-resistant 430 stainless steel did not change significantly, but the corrosion rate was significantly increased, and the adhesion of the passivation film also decreased. Compared with Example 1, Comparative Example 4 replaced the modified Al2O3 in the passivation solution with Al2O3 and replaced the fluorinated epoxy acrylate resin in the passivation solution with acrylic resin. The corrosion rate increased significantly and the adhesion of the passivation film decreased significantly. Compared with Example 1, the 430 stainless steel in Comparative Example 5 did not contain cerium powder and lanthanum powder, and was not coated with passivation solution. The tensile strength of the 430 stainless steel produced was significantly reduced, and the corrosion rate was significantly increased. Compared with Example 1, the blank control group showed the highest corrosion rate; In summary, the addition of rare earth elements cerium and lanthanum to the stainless steel billet in this application can promote the improvement of the tensile strength of the corrosion-resistant 430 stainless steel, the setting of the passivation film can promote the improvement of the corrosion resistance of the corrosion-resistant 430 stainless steel, and the setting of the passivation liquid components is conducive to improving the adhesion of the passivation film, thereby comprehensively improving the corrosion resistance of stainless steel.
[0045] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
Claims
1. A manufacturing process for corrosion-resistant 430 stainless steel for water heater core plates, characterized in that: Includes the following steps: Step 1: Mix raw materials other than rare earth elements, melt them, heat them, add rare earth elements under nitrogen atmosphere protection, heat them again, pour and cool them to obtain stainless steel billet; Step 2: The stainless steel billet is subjected to heat treatment, rough rolling, finish rolling, annealing, pickling and drying in sequence to obtain 430 stainless steel matrix; Step 3: Coat the surface of the 430 stainless steel substrate with passivation solution, dry, let stand, and form a passivation film to obtain corrosion-resistant 430 stainless steel; The passivation solution comprises the following components by mass: 15~30 g / L modified Al2O3, 220~260 g / L fluorinated epoxy acrylate resin, 8~15 g / L 2-aminothiazole, and 1.0~1.3 g / L nickel acetate, with deionized water as the solvent.
2. The preparation process of corrosion-resistant 430 stainless steel for water heater core according to claim 1, characterized in that: The modified Al2O3 is obtained by the following process: S1: Under a nitrogen atmosphere, 1,2-diaminoimidazole and tetrahydrofuran were mixed, and 3-isocyanate-propyltriethoxysilane was added while stirring. The mixture was heated and stirred to react. After the reaction was completed, the mixture was rotary evaporated to obtain an imidazole coupling agent. S2: Mix carboxymethyl chitosan, imidazole coupling agent, and ethanol aqueous solution, adjust the pH to 4.0~4.5 with glacial acetic acid, disperse by ultrasonication, hydrolyze by stirring, react by stirring in a water bath, centrifuge and dry after the reaction is completed to obtain modified carboxymethyl chitosan; S3: Mix deionized water and modified carboxymethyl chitosan, stir evenly, add Al2O3, heat and stir to react, and obtain modified Al2O3.
3. The preparation process of corrosion-resistant 430 stainless steel for water heater core according to claim 1, characterized in that: The preparation process of the fluorinated epoxy acrylate resin is as follows: Under a nitrogen atmosphere, xylene and butyl acetate are mixed and heated to 80-90°C. Then, dodecafluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate and azobisisobutyronitrile are added over 3-4 hours. The mixture is kept at this temperature to obtain a fluorinated epoxy acrylic resin.
4. The preparation process of corrosion-resistant 430 stainless steel for water heater core according to claim 2, characterized in that: In S1, the ratio of 1,2-diaminoimidazole, tetrahydrofuran, and 3-isocyanate-propyltriethoxysilane is (3~5) g: (45~55) mL: (6~10) g.
5. The preparation process of corrosion-resistant 430 stainless steel for water heater core according to claim 2, characterized in that: In S2, the ratio of carboxymethyl chitosan, imidazole coupling agent, and ethanol aqueous solution is (1~3) g: (3~9) g: 100 mL.
6. The preparation process of corrosion-resistant 430 stainless steel for water heater core according to claim 2, characterized in that: In S3, the ratio of deionized water, modified carboxymethyl chitosan, and Al2O3 is 35mL: (0.5~1.0)g: (0.5~1.0)g.
7. The preparation process of corrosion-resistant 430 stainless steel for water heater core according to claim 3, characterized in that: The mass ratio of xylene, butyl acetate, dodecafluoroheptyl methacrylate, butyl acrylate, glycidyl methacrylate, and azobisisobutyronitrile is (2.0~3.0):1:(0.8~1.2):(0.6~0.8):(0.8~1.0):(0.08~0.12).
8. The preparation process of corrosion-resistant 430 stainless steel for water heater core according to claim 1, characterized in that: In step 3, the thickness of the passivation film is 0.4~0.8μm.
9. The preparation process of corrosion-resistant 430 stainless steel for water heater core according to claim 1, characterized in that: The rare earth elements are Ce and La; The stainless steel billet comprises the following mass percentages: 0.04~0.10% C, 0.25~0.65% Si, 0.10~0.15% Mn, 0.010~0.015% P, 0.09~0.12% Ni, 16.0~17.0% Cr, 0.010~0.012% Ce, 0.005~0.007% La, with the balance being Fe.
10. The water heater core plate is made of corrosion-resistant 430 stainless steel, characterized in that: The preparation process according to any one of claims 1 to 9 is used.
